Peritoneal flap mesh hernioplasty: A reliable option for difficulty in closure of complex ventral hernia: A case report - Khanal, Bhawani; Agrawal, Sunit; Sah, Suresh; Gurung, Roshan; Gupta, Rakesh Kumar (Journal of Gandaki Medical College-Nepal, 2020)
Peritoneal flap mesh hernioplasty is a technique to deal with complex ventral hernias in which primary closure of the defect is not attainable. We are here presenting a case report of a 50-year-old gentleman with huge complex ventral hernia with loss of domain. The patient also had overlying ulcerated and blackish colored skin. Botulinum toxin was infiltrated into the muscles of anterior abdominal wall and was followed by peritoneal flap mesh hernioplasty after one month. The final outcome was complete closure of the midline with a healthy skin with no evidence of abdominal compartment syndrome. There was no evidence of early recurrence on follow up.Owing to the favorable outcome in this case, suitability of peritoneal flap mesh hernioplasty technique in treatment of complex ventral hernia could be explored further where closure of the primary defect is difficult.